Influence of Incentives and Work Motivation on Employee Productivity at PT Panelindo Graha Nusantara - Bimantoro; Mulyati; Tarmizi, Rasyid; Mutiara Zahrani, Amelia (APTISI Transactions on Management (ATM), 2025)
This study investigates the impact of incentives and work motivation on em- ployee productivity at PT Panelindo Graha Nusantara, a company operating in the electrical panel manufacturing sector. The importance of employee produc- tivity in achieving organizational goals motivates this research, particularly in the context of human resource management strategies. The objective is to analyze both the partial and simultaneous effects of incentives and motivation on sample of 72 employees. Data were collected using structured questionnaires and analyzed through classical assumption tests, multiple linear regression, and determination coefficient analysis using SPSS software. The results indicate that incentives and work motivation both have significant positive effects on employee productivity individually and simultaneously. The partial tests show significance with t-values exceeding the critical t-value, and the simultaneous test reveals a significant F-value well above the threshold. The coefficient of determination suggests that 65.3% of the productivity variance can be explained by these two variables. In conclusion, the findings emphasize the critical role of properly designed incentive systems and motivation strategies in enhancing employee productivity. These insights provide valuable guidance for managers aiming to optimize workforce performance in similar industrial settings